Stories I Might Regret Telling You: A Memoir - Wainwright, Martha (Hachette Books, 2022)
The singer-songwriter's heartfelt memoir about growing up in a bohemian musical family and her experiences with love, loss, motherhood, divorce, the music industry, and more. Born into music royalty, the daughter of folk legends Kate McGarrigle and Loudon Wainwright III and sister to the highly-acclaimed and genre-defying singer Rufus Wainwright, Martha grew up in a world filled with such incomparable folk legends as Leonard Cohen; Suzzy Roche, Anna McGarrigle, Richard and Linda Thompson, Pete Townshend, Donald Fegan, and Emmylou Harris. It was within this loud, boisterous, carny, musical milieu that Martha came of age, struggling to find her voice until she exploded on the scene with her 2005 debut critically acclaimed album, Martha Wainwright, containing the blistering hit, 'Bloody Mother F*cking Asshole,' which the Sunday Times called one of the best songs of that year. Her successful debut album and the ones that followed such as Come Home to Mama, I Know You're Married But I've Got Feelings Too, and Goodnight City came to define Martha's searing songwriting style and established her as a powerful voice to be reckoned with. In her memoir, Stories I Might Regret Telling You, Martha digs into the deep recesses of herself with the same emotional honesty that has come to define her music. She describes her tumultuous public-facing journey from awkward, earnest, and ultimately rebellious daughter, through her intense competition and ultimate alliance with her brother, Rufus, to the indescribable loss of their mother, Kate, and then, finally, discovering her voice as an artist. With candor and grace, Martha writes of becoming a mother herself and making peace with her past struggles with Kate and her former self, finally understanding and facing the challenge of being a female artist and a mother. Ultimately, Stories I Might Regret Telling You offers readers a thoughtful and deeply personal look into the extraordinary life of one of the most talented singer-songwriters in music today.